2021
DOI: 10.37897/rjn.2021.2.23
|View full text |Cite
|
Sign up to set email alerts
|

The Challenging Diagnosis of Dysferlinopathy – A Case Report

Abstract: Objectives. Dysferlinopathies are a group of rare genetic myopathies characterized by muscle weakness and atrophy with four distinct clinical phenotypes: Miyoshi myopathy, limb girdle muscular dystrophy type 2B, distal myopathy with anterior tibial onset and an intermediate proximo-distal phenotype. We report a case of dysferlinopathy and discuss relevant clinical, pathological and genetic data. Material and methods. We present the case of a 36 years old man with more than ten years history of progressive musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Misdiagnosis is a concern with dysferlinopathies due to symptomological overlaps with conditions like polymyositis (PM), other limb-girdle muscular dystrophies (LGMDs), and even Charcot–Marie–Tooth disease (CMT) [ 43 , 50 , 58 , 59 ]. The distinction lies in the absence of elevated CK levels and specific sarcolemma upregulation in CMT [ 43 , 59 ]. Electromyographic (EMG) studies, complemented by CT and MRI, aid in differentiating dysferlinopathy from CMT [ 59 ].…”
Section: Dysferlinopathies: Clinical Landscape and Phenotypic Variabi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Misdiagnosis is a concern with dysferlinopathies due to symptomological overlaps with conditions like polymyositis (PM), other limb-girdle muscular dystrophies (LGMDs), and even Charcot–Marie–Tooth disease (CMT) [ 43 , 50 , 58 , 59 ]. The distinction lies in the absence of elevated CK levels and specific sarcolemma upregulation in CMT [ 43 , 59 ]. Electromyographic (EMG) studies, complemented by CT and MRI, aid in differentiating dysferlinopathy from CMT [ 59 ].…”
Section: Dysferlinopathies: Clinical Landscape and Phenotypic Variabi...mentioning
confidence: 99%
“…The distinction lies in the absence of elevated CK levels and specific sarcolemma upregulation in CMT [ 43 , 59 ]. Electromyographic (EMG) studies, complemented by CT and MRI, aid in differentiating dysferlinopathy from CMT [ 59 ]. While a Western blot determines the presence or absence of dysferlin protein in tissues, genetic screening, complemented by advanced sequencing, is necessary to pinpoint specific mutations [ 31 , 59 , 60 , 61 , 62 ].…”
Section: Dysferlinopathies: Clinical Landscape and Phenotypic Variabi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients’ creatine kinase (CK) level is also on average 54 times higher than that of control groups [ 31 ], and they start using a cane to walk in their thirties and become wheelchair-bound in their forties or, on average, 21 years after onset [ 33 ]. The phenotype is located in the skeletal muscles, and the heart remains unaffected, with normal results for electrocardiogram and echocardiogram [ 34 ]. However, a 3-year study showed that up to 30% of patients have a reduced forced vital capacity (FVC) and that up to 58% of patients have a cardiac P-wave abnormality, which can be a risk factor for atrial flutter [ 35 ].…”
Section: Dysferlinopathymentioning
confidence: 99%
“…Another possible but rare misdiagnosis for dysferlinopathy can be Charcot–Marie–Tooth disease (CMT), since both diseases involve a distal weakness phenotype [ 34 ]. One way to tell them apart is that CMT does not cause a high creatine kinase level nor the sarcolemma upregulation of major histocompatibility complex class I (MHC I) like dysferlinopathy does.…”
Section: Dysferlinopathymentioning
confidence: 99%